Clinical and functional state of the retina after inadequate laser coagulation of peripheral vitreochorioretinal dystrophies. Part 2. A study of microcirculation of the macular area - V. V. Neroev; G. Yu. Zakharova; T. D. Okhotsimskaya; M. V. Zueva; I. V. Tsapenko; V. A. Fadeeva; B. M. Magamadov (Российский офтальмологический журнал, 2020)
Purpose: to evaluate the effect of inadequately performed laser coagulation (LC) of peripheral vitreochorioretinal dystrophies (PVCRD) on the microcirculation of the macular region in patients with myopia. Material and methods. The state of the microvascular bed was investigated by OCT angiography (OCT-A), Angio Retina mode, scanning area 6 x 6 mm. The density of the surface vascular plexus was evaluated using a 9-quadrant protocol and an ETDRS grid. The parameters of the foveolar avascular zone (FAS) were determined. OCT-A of the retina was performed in 18 patients with PVCRD who had signs of inadequate retinal LC, such as hypercoagulation, an excessive number of coagulates with minimal changes in the retina, or massive LC in normal fundus eyes documented in their case histories. The research results were compared with the data of OCT-A obtained in 10 patients with myopia without signs of PVCRD (controls 1) and in 75 healthy individuals (controls 2). Results. In all patients with myopia (in the main group and controls 1), blood flow density indices were, respectively, 10–20 and 2–14 % lower than those in controls 2. The maximal decrease in blood flow density was found in the foveal zone in cases of hyper LC (p < 0.05). Also, in the eyes with excessive LC a significant expansion of the FAS and thinning of the retina were revealed. Conclusion. The results of the OCT-A study point to a negative effect of hyper LC of the PVCRD on the state of the microvasculature of the retina in the central zone. The obtained data correlate with our results of electrophysiological studies presented in the first part of this paper [ROJ, 2020; 13 (2): 45–52], which indicate functional changes in the fovea zone after inadequate laser coagulation in the peripheral areas of the retina.